Men with high dark triad personality traits can accurately infer dark triad traits from other people’s faces - Masui, Keita; Yoshizumi, Ryusei; Nakajima, Hina (Frontiers in Psychology, 2024)
The literature suggests that people can accurately infer dark triad (DT) personality traits from other peoples' faces. Using a self-report scale, this study investigated the impact of participants' DT personality traits on their ability to accurately infer other peoples' DT traits from facial cues. Methods: We created composite facial photographs of Japanese people with varying Machiavellianism, psychopathy, and narcissism scores. The Japanese participants (N = 170) assessed these three DT traits in the facial photographs and completed a questionnaire that assessed their own DT traits. Results: The results indicated that the participants could accurately infer all three DT traits from female faces but not from male faces. Male participants showed a positive correlation between accurate inferences of other men's Machiavellianism and their own DT traits. In contrast, female participants showed a negative correlation between correct inferences of men's DT traits and their own DT traits. Discussion: These findings offer novel insights into human evolutionary and social adaptations.